2015
DOI: 10.1021/acs.jcim.5b00092
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Based Virtual Screening and Biological Evaluation of a Calpain Inhibitor for Prevention of Selenite-Induced Cataractogenesis in an in Vitro System

Abstract: Calpains belong to the family of calcium-dependent, structurally related intracellular cysteine proteases that exhibit significant functions in evolution of different types of cataracts in human as well as animal models. Application of calpain inhibitors generated through a virtual screening workflow may provide new avenues for the prevention of cataractogenesis. Hence, in the current study, compounds were first screened for potent calpain inhibitory activity by employing a structure-based approach, and the sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 70 publications
(112 reference statements)
0
20
0
Order By: Relevance
“…In the different earlier studies, the Glide score had been used as a reliable function for sorting of a compound data set against drug target protein. Glide scoring has been found effective for ranking inhibitors (19). Hence, we ranked the hits according to the Glide XP score toward LdAPx.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the different earlier studies, the Glide score had been used as a reliable function for sorting of a compound data set against drug target protein. Glide scoring has been found effective for ranking inhibitors (19). Hence, we ranked the hits according to the Glide XP score toward LdAPx.…”
Section: Resultsmentioning
confidence: 99%
“…The docking and scoring were performed by using default docking parameters. The final scoring of compounds was done based on XP output (19). The interaction (Glide XP score) of known APx inhibitor 4-triazol-5-amino (12) was taken as a positive control in our docking studies.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study demonstrated that virtual screening is more significant than high-throughput screening because of less time consumption and cost effectiveness 15,16 . Receptor-based virtual screening for various targets including proteases has demonstrated the success rate of in silico studies 17 .…”
Section: Molecular Docking and Virtual Screeningmentioning
confidence: 99%
“…Initially, the standard precision (SP) and extra-precision (XP) docking were performed to calculate the Glide score and Glide energy. MAP kinase (16). Hence, in the present study, we have ranked the inhibitors based on their glide score.…”
Section: Molecular Docking and Virtual Screeningmentioning
confidence: 99%